Ratio of isolated photon cross sections in pp macro collisions at square root of s = 630 and 1800 GeV. - Abazov, V; Abbott, B; Abdesselam, A; Abolins, M; Abramov, V; Acharya, B; Adams, D; Adams, M; Ahmed, SN; Alexeev, G; Alton, A; Alves, G; et al. (2001)
The inclusive cross section for production of isolated photons has been measured in pp macro collisions at square root of s = 630 GeV with the D0 detector at the Fermilab Tevatron Collider. The photons span a transverse energy (E(T)) range from 7-49 GeV and have pseudorapidity absolute value of eta < 2.5. This measurement is combined with the previous D0 result at square root of s = 1800 GeV to form a ratio of the cross sections. Comparison of next-to-leading-order QCD with the measured cross section at 630 GeV and the ratio of cross sections show satisfactory agreement in most of the E(T) range.